Hydropower Development and the Loss of Fisheries in the Mekong River Basin - Campbell, Ian; Barlow, Chris (Frontiers in Environmental Science, 2020)
Development of large scale hydropower is proceeding rapidly in the Mekong basin without adequate consideration of the severe and cumulative impacts the dams and reservoirs will, and are already beginning to, have on biodiversity, livelihoods and the economies of the lower Mekong countries. Migratory aquatic species will be particularly affected, and global experience indicates that fishways proposed for large mainstream and tributary dams will not provide effective amelioration. An offset strategy of remediating small weirs, flood control devices, regulators and irrigation works on tributaries and flood plains is more likely to be an effective and economically efficient means of supplementing fisheries to compensate for the negative impact of mainstream dams. Mainstream hydropower developments may result in future stranded assets, high electricity costs and even threaten the sovereignty of lower Mekong countries.